Pengaruh Mol K3Fe(CN)6 pada Sintesis Zat Warna Biru Prusia berbahan Pasir Besi Muara Pantai Sunur Pariaman - Nafis Sudirman; Syamsi Aini (Jurnal Periodic Jurusan Kimia UNP, 2022)
The aim of the study was to determine the effect of moles of K3Fe(CN)6 on the Prussian blue color, to obtain the optimum synthesis conditions. Coprecipitation and centrifugation methods for separating pigments from solvents. Fe3O4 was reacted with 96% H2SO4 to obtain Fe2+ ions, then reacted with K3Fe(CN)6, producing Prussian Blue. This study varied 3 samples of K3Fe(CN)6, the variation results were referred to as M1, M2 and M3. In sample M1, 3.037 mmol K3Fe(CN)6 was reacted at 30.37 mM. For sample M2, 9.87 mmol K3Fe(CN)6 30.37 mM was reacted with 4.56 mmol FeSO4 0.018 mM, 250 mL. In sample M3, reacted with 12.21 mmol K3Fe(CN)6 30.37 mM. In the variation of K3Fe(CN)6, the optimum is in the M2 sample. The maximum UV-Vis absorbance of M2 products is at 747 nm, according to the standard absorbance wavelength of Prussian Blue (680-740 nm), and the absorbance is relatively high.Keywords — iron sand, potassium ferricyanide, prussian blue, pigment